AB0849 Retention rate of adalimumab, etanercept and infliximab at 5 years in patients with ankylosing spondylitis: Report from the rhumadata computerized database. (23rd January 2014) - Choquette, D.; Sauvageau, D.; Raynauld, J.-P.
Abstract : Background: Most of the data exploring the recent development of the treatment of ankylosing spondylitis come from randomized placebo controlled phase III trials. The patients who are randomized in these trial are typically very different from those that we see and treat in our daily clinical practice. The data coming from these trial is also usually for the short term, maximally one to two years. At the Institute of Rheumatology of Montreal, we have been collecting data of patients suffering from ankylosing spondylitis using a locally developed software named Rhumadata. The software permits data collection directly from patients as well those from the healthcare practitionners (Nurses, Physicians, etc) Objectives: The primary objective of this study is to evaluate the retention rate of patients suffering from ankylosing spondylitis after 5 years of exposure to either adalimumab (ADA), etanercept (ETA)or infliximab (INF). The secondary objective is to evaluate if all patients exposed to each biologic agents are similar or if there are characteritics that are different at entry between adalimumab, etanercept and infliximab Methods: Using the Rhumadata software, we extracted all patients suffering from ankylosing spondylitis as diagnosed by his rheumatologist.These patients had to be exposed to either adalimumab, etanercept or infliximab as first exposure ever to a biologic agent. Data extraction period ranges from 2005 up to 2011. All patients had to exposed to at least two different NSAIDS for a minimum of three months each to be eligible to received an anti-TNF agents. Their baseline BASDAI had to be equal or superior to 4 at entry. The different variables extracted from Rhumadata for each cohorts are: Number of patients, duration of disease, age at the time of anti-TNF introduction, gender, HLA-B27 status, morning stiffness duration, VAS pain evaluation, BASDAI and BASFI. Results: 119 patients suffering from ankylosing spodylitis and exposed to either ADA, ETA or INF were found and extracted from the Database. 53 patients were prescribed ADA, 18 ETA and 48 INF. More than 75% of patients of each cohort were of male gender and the Mean age is 46 (SD 11). No significant differences in demographics and clinical variables were found between each group at baseline (T-test). Proportion of patients remaining on the same anti-TNF agent at 1 year is 80%, 2 years 70% and 5 years 55% (p=.988) (Kaplan-meier analysis). Conclusions: Adalimumab, etanercept and infliximab retention rates at 1, 2 and 5 years for patients with ankylosing spondylitis are similar. Each of these agent is a adequate option in the treatment of ankylosing spondylitis. Disclosure of Interest: None Declared